Generation of Lactobacillus plantarum strains with improved potential to target gastrointestinal disorders related to sugar malabsorption. (April 2017) - Šeme, Helena; Bogovič Matijašić, Bojana; Švigelj, Karmen; Langerholc, Tomaž; Fujs, Štefan; Horvat, Jaka; Zlatić, Emil; Gjuračić, Krešimir; Petković, Hrvoje; Štempelj, Mateja; Kos, Blaženka; Šušković, Jagoda; et al.
Abstract: Malabsorption of dietary sugars is a common cause of gastrointestinal discomfort, affecting up to one in three people with debilitating symptoms, such as abdominal pain, osmotic diarrhoea, bloating and flatulence. Besides dietary interventions, it has been suggested that ingestion of lactobacilli may alleviate these symptoms. The objectives of this study were to generate strains with improved potential to ameliorate sugar malabsorption related gastrointestinal disorders. Initial selection was made from 183 natural isolates of lactic acid bacteria, on the basis of broad sugar fermentation ability, absence of gas production, gastrointestinal survival and susceptibility to important medical antimicrobials. Two strains of L. plantarum (KR6 and M5) exhibited favourable characteristics for all criteria, and were further optimised through random mutagenesis and selection approaches. Ultraviolet light (UV) exposure resulted in mutants characterized by better survival (for 1.9 log and 1.4 log) in gastrointestinal conditions. Subsequent exposure to ethyl methanesulfonate (EMS) provided mutants with greater tolerance to glucose induced catabolic repression. UV and UV-EMS mutants of L. plantarum M5 showed improved adhesion ability. As a result of this optimisation, L. plantarum MP2026 and L. plantarum MP2420 have been identified as promising candidates for probiotics, intended for alleviation of gastrointestinal discomfort originating from sugar malabsorption. Graphical abstract: Highlights: Lactobacillus plantarum mutants were generated by random mutagenesis with UV and EMS. Mutant strains had improved survival and reduced catabolite repression. UV mutagenesis leaded to improved adhesion to H4-1 human intestinal cell line. New strains are probiotic candidates for alleviation of sugar malabsorption symptoms.